Isomorphism and Sustainable Development Practices of Small Businesses in Limpopo Province, South Africa - Masocha, Reginald (University of Limpopo, 2019)
Refer to the document
Thesis ((Ph.D. Commerce (Business Management)) ,2019
Keywords: Isomorphism; Sustainable development; Small businesses; Limpopo Province; South Africa; Small businesses --South Africa; Curry-Howard Isomorphism